2017
DOI: 10.1016/j.chom.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

SMYD2-Mediated Histone Methylation Contributes to HIV-1 Latency

Abstract: Summary Transcriptional latency of HIV is a last barrier to viral eradication. Chromatin-remodeling complexes and post-translational histone modifications likely play key roles in HIV-1 reactivation but the underlying mechanisms are incompletely understood. We performed a RNAi-based screen of human lysine methyltransferases and identified the SET and MYND domain-containing protein 2 (SMYD2) as an enzyme that regulates HIV-1 latency. Knockdown of SMYD2 or its pharmacological inhibition reactivated latent HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 67 publications
3
83
0
Order By: Relevance
“…Other epigenetic modifications have also been implicated in HIV latency (Blazkova et al, 2009; Boehm et al, 2017; Pearson et al, 2008); it is likely that some of these also regulate viral phenotypic diversity. One possibility is that different chromatin modifications determine different timescales of provirus epigenetic memory (Bintu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other epigenetic modifications have also been implicated in HIV latency (Blazkova et al, 2009; Boehm et al, 2017; Pearson et al, 2008); it is likely that some of these also regulate viral phenotypic diversity. One possibility is that different chromatin modifications determine different timescales of provirus epigenetic memory (Bintu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…“Reader” can specifically recognize chromatin modifications, whereas “eraser” can remove modifications. The Boehm et al (2017) study indicates that SMYD2, and likely L3MBTL1, are novel regulators and pharmacological targets of HIV-1 latency. Epigenetic events under the control of host cell coregulators of HIV transcription and latency are of particular interest for “shock and kill” approaches of HIV-1 eradication for a functional cure.…”
Section: Figurementioning
confidence: 93%
“…In this issue of Cell Host & Microbe, Boehm et al (2017) report on an RNAi screen to query KMTs involved in HIV latency reversal and identify SMYD2, a member of a family of non-canonical SET-domain-containing chromatin modifiers, as an HIV provirus corepressor. Knockdown of SMYD2 relieves HIV latency in model reporter cell lines, and the bioavailable SMYD2 inhibitor AZ391 increases cellular transcript levels of HIV in CD4+ T cells from patients with suppressed viral load.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials with these agents, albeit have shown modest to no viral rebound. Other epigenetic modifiers like bromodomain inhibitors [17,18] and SMYD inhibitors (methylation blockers) [19] have also been the target for HIV reactivation with limited success so far.…”
Section: Editorialmentioning
confidence: 99%